Transitions of Care in Heart Failure. (March 2015) - Albert, Nancy M.; Barnason, Susan; Deswal, Anita; Hernandez, Adrian; Kociol, Robb; Lee, Eunyoung; Paul, Sara; Ryan, Catherine J.; White-Williams, Connie
<x xml:space="preserve">Abstract</x> In patients with heart failure (HF), use of 30-day rehospitalization as a healthcare metric and increased pressure to provide value-based care compel healthcare providers to improve efficiency and to use an integrated care approach. Transition programs are being used to achieve goals. Transition of care in the context of HF management refers to individual interventions and programs with multiple activities that are designed to improve shifts or transitions from one setting to the next, most often from hospital to home. As transitional care programs become the new normal for patients with chronic HF, it is important to understand the current state of the science of transitional care, as discussed in the available research literature. Of transitional care reports, there was much heterogeneity in research designs, methods, study aims, and program targets, or they were not well described. Often, programs used bundled interventions, making it difficult to discuss the efficiency and effectiveness of specific interventions. Thus, further HF transition care research is needed to ensure best practices related to economically and clinically effective and feasible transition interventions that can be broadly applicable. This statement provides an overview of the complexity of HF management and includes patient, hospital, and healthcare provider barriers to understanding end points that best reflect clinical benefits and to achieving optimal clinical outcomes. The statement describes transitional care interventions and outcomes and discusses implications and recommendations for research and clinical practice to enhance patient-centered outcomes.